Entrepreneurial Intention Among Generation Z In Bekasi City: The Roles Of Self-Efficacy, Family Environment, And Creativity - Septiani Sunandar; Kristiana Widiawati (Universitas Indonesia Membangun (Inaba), 2026)
Bekasi City recorded an unemployment rate of 7.33%, which was higher than the national average. At the national level, young people, predominantly Generation Z, represent the age group with the highest unemployment rate. Against this background, this study examines the relationship between self-efficacy, family environment, and creativity and entrepreneurial intention among Generation Z in Bekasi City. A quantitative approach was employed involving 160 Generation Z respondents aged 18–29 years residing in Bekasi City, selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 29. The results indicate that self-efficacy, family environment, and creativity are each positively associated with entrepreneurial intention, both individually and collectively. Among these variables, creativity exhibited the largest standardized regression coefficient (β = 0.392), indicating a relatively stronger association with entrepreneurial intention within the analyzed sample. Overall, the findings suggest that self-efficacy, family environment, and creativity are statistically associated with entrepreneurial intention among Generation Z in Bekasi City.